DECOMPOSITION OF COMPLETE GRAPHS AND COMPLETE BIPARTITE GRAPHS INTO COPIES OF Pn3 or S2Pn3 AND HARMONIOUS LABELING OF K2+ Pn - Selvaraju, P.; Sethuraman, G. (IndoMS, 2011)
Pdf AbstractDOI :Â http://dx.doi.org/10.22342/jims.0.0.23.109-122